1991
DOI: 10.1037/1040-3590.3.4.596
|View full text |Cite
|
Sign up to set email alerts
|

Multiple measures of malingering on a forced-choice test of cognitive ability.

Abstract: This article describes how a 2-alternative, forced-choice response technique was applied to a nonverbal test of cognition in order to generate measures of noncompliance and serve as a means to detect malingering. Three studies were conducted. Study 1 used a 2-alternative, forced-choice test format comprising 100 nonverbal test items of a hierarchy of difficulty presented in a random order. In a simulation study, a combination of decision rules regarding (a) performance curves slope; (b) a measure of response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Those in the SC group were asked to believably feign cognitive impairment during the assessment in an attempt to obtain imaginal financial compensation, and were given instructions describing typical symptomatology associated with mild TBI (e.g., memory problems). Those in the TC simulation group were instructed to feign cognitive impairment during the assessment in an attempt to obtain imaginal financial compensation, and were given instructions describing effective test-taking strategies that would help them avoid detection (see test-coaching used by Frederick & Foster, 1991). The specific instructions for the three groups are available from the first author.…”
Section: Methodsmentioning
confidence: 99%
“…Those in the SC group were asked to believably feign cognitive impairment during the assessment in an attempt to obtain imaginal financial compensation, and were given instructions describing typical symptomatology associated with mild TBI (e.g., memory problems). Those in the TC simulation group were instructed to feign cognitive impairment during the assessment in an attempt to obtain imaginal financial compensation, and were given instructions describing effective test-taking strategies that would help them avoid detection (see test-coaching used by Frederick & Foster, 1991). The specific instructions for the three groups are available from the first author.…”
Section: Methodsmentioning
confidence: 99%
“…Various versions of the PDRT (Binder, 1993;Binder & Willis, 1991;Greiffenstein et al, 1994;Rose, Hall, & Szalda-Petree, 1995) and the Hiscock procedure (Guilmette, Hart, & Giuliano, 1993;Hiscock & Hiscock, 1989;Martin, Bolter, Todd, Gouvier, & Niccolls, 1993;Prigatano & Amin, 1993;Slick, Hopp, Strauss, Hunter, & Pinch, 1994) have been repeatedly validated with encouraging results. Studies employing a variety of forced-choice procedures have also found that the majority of malingerers do not obtain scores significantly below chance (Binder & Willis, 1991;Frederick & Foster, 1991;Guilmette et al, 1993;Martin et al, 1993;Slick et al, 1994) and have provided cutoff scores for assessment of motivation.…”
mentioning
confidence: 97%
“…Additionally, we did not provide our sophisticated simulating subjects with specific test-taking strategies to avoid detection. Provision of such information, as has been done by some investigators (Frederick & Foster, 1991;Martin, Bolter, Todd, & Gouvier, 1992), may have produced different results.…”
Section: Discussionmentioning
confidence: 99%